Research on Systemic Risks’ Spillover Effects of China’s Commercial Banks under COVID-19 - Ma, Lei (2020)
During the financial crisis in 2008, under the influence of the domino effect, multinational banks were significantly impacted by systemic risks, which had a negative impact on the real economy of various countries. At present, the global outbreak of the COVID-19 makes many countries face systemic risks again. It shows the importance of macro-prudential supervision of systemic risk, and the premise of adequate supervision of systemic risk is to measure the risk spillover effect accurately. By studying the measurement of systemic risk, regulators can judge the degree of risk spillover of China's banks in the event of COVID-19 to strictly control the banks with large risk spillovers and better prevent systemic risks.